Динамічна аутентифікація за клавіатурним почерком з використанням критерію манна-вітні - Маслій, Д. В. (ХНУРЕ, 2019)
In work the algorithm of keystroke authentication based on the Mann-Whitney U-test is developed. The algorithms of formation of the user profile and its authentication has been designed.